Kamus istilah telekomunikasi - Saydam, Gouzali; Indonesia (Bandung, Jawa Barat : Pustaka Reka Cipta, 2010)
Indonesian dictionary of telecommunication terms.
Includes the text of: Undang-Undang Tentang Telekomunikasi (1999).
Includes bibliographical references (p. 605-607).
Keywords: Telecommunication -- Dictionaries -- Indonesian; Telecommunication -- Dictionaries; English language -- Dictionaries -- Indonesian